The Schnauzenorgan-response of Gnathonemus petersii - Röver Timo; Nöbel Sabine; Engelmann Jacob; Emde Gerhard (Frontiers in Zoology, 2009)
Abstract Background Electric fish navigate and explore their dark and turbid environment with a specialised electric sense. This active electrolocation involves the generation and perception of an electric signal and fish have proven to be useful model systems for the investigation of sensory-motor interactions. A well studied example is the elephantnose fish, Gnathonemus petersii, which has a characteristic and unique elongated chin covered with hundreds of electroreceptor organs. This highly moveable so-called Schnauzenorgan constitutes the main fovea of the active electrosensory system. Here we present first evidence for a sensory-motor loop relating active electrical sensing to active motor exploration of the environment. Results Both anatomical and behavioural evidence have shown that the moveable Schnauzenorgan is crucial for prey localization. Here we show for the first time that a motor response (Schnauzenorgan-response, SOR) can be elicited by novel electrosensory stimuli. The SOR could be triggered with highest reliability by novel electrical stimuli near the Schnauzenorgan and, to a lesser extend, near the head of the animal. The probability of evoking the response depended on the magnitude of the amplitude change of the electric input, with bigger changes eliciting SORs more reliably. Similarly, increasing the distance of the stimulus reduced the response. In this respect the SOR is comparable to the well described novelty response, a transient acceleration of the production rate of electric signals, although the latter occurs at a shorter delay and can also be evoked by non-electrical stimuli. Conclusion Our experiments show a novel motor response that is mediated by the active electric sense of Gnathonemus petersii. This response will allow a detailed analysis of the neural system underlying direct interaction between sensory and motor processes in future experiments.